Factors Affect In IELTS Test For Students of STIKOM Uyelindo Kupang - Heni, Heni (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
IELTS (International English Language Testing System) is a standardized English language proficiency test which is a prerequisite for continuing study or work. There are still many people who experience difficulties in carrying out the IELTS test to achieve a score above 6. The aim of the research is to know what are the factors that affect the result of students IELTS test. This research wants to find out what factors influence students' mastery of IELTS material. The method used in this research is descriptive qualitative. Qualitative descriptive research uses a series of methods to specify and describe data findings that occur in the field without providing experimental treatment. There are four IELTS materials given during the test, including: reading, writing, speaking, and listening. These four materials require strategies in their implementation and each has their own difficulties in mastering them. This research will be conducted at STIKOM Uyelindo Kupang with the research object being students of the Informatics and Information Systems Engineering Study Program Semester 2. It is hoped that this research will provide readers with an understanding regarding the success factors in carrying out the IELTS test.